Pemanfaatan Teknologi Mendukung Merdeka Belajar: Implementasi Kampus Mengajar di SDIT Anak Sholeh 2 Mataram - Akbar, Aulia Rahmayani; Yuniarsih, Dilla Khairunnisa; Hidayah, Fadila (Pendidikan Matematika FKIP Universitas Mataram, 2025)
The use of technology becomes crucial in supporting the implementation of this program, especially in the digital era. This study aims to examine the use of technology in supporting Merdeka Belajar, specifically the study of the implementation of the Kampus Mengajar activities at SDIT Anak Sholeh 2 Mataram. This qualitative research with a case study method uses data collected through observation, interviews with students, teachers, and the principal, as well as documentation studies. The results show that technology is used in various aspects, including: (1) creating interactive learning media, (2) utilizing digital learning platforms, and (3) developing students' digital literacy. The use of technology has a positive impact in creating a more interactive, effective, and enjoyable learning process. However, there are challenges that need to be addressed, such as limited infrastructure and the digital skills gap. This research provides recommendations for improving the quality of the Kampus Mengajar program and the implementation of Merdeka Belajar in Indonesia